2006
DOI: 10.1097/01.psy.0000195834.37094.a4
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Road From Childhood Trauma to Adult Somatization: The Role of Attachment

Abstract: Objective: This study tested whether insecure attachment mediates the link between childhood trauma and adult somatization. Methods: A community sample of 101 couples completed self-report measures, including the Relationship Scales Questionnaire, the Childhood Trauma Questionnaire, the Somatic Symptom Inventory, the Beck Depression Inventory, and the Conflict Tactics Scale. Results: Childhood trauma was associated with higher levels of somatization and insecure attachment. Insecure attachment style was also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
128
3
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(150 citation statements)
references
References 32 publications
11
128
3
8
Order By: Relevance
“…Indeed, clinical reports reveal that patients with chronic pain are more sensitive to social pain (Asmundson et al 1996) and that those who tend to be more sensitive to social pain also report more somatic symptoms, including pain (Ciechanowski et al 2002, Ehnvall et al 2009, Waldinger et al 2006. Experimental studies have shown that individuals who are more sensitive to experimental pain self-report higher levels of social pain in response to social exclusion (Eisenberger et al 2006).…”
Section: Consequences Of An Overlapmentioning
confidence: 99%
“…Indeed, clinical reports reveal that patients with chronic pain are more sensitive to social pain (Asmundson et al 1996) and that those who tend to be more sensitive to social pain also report more somatic symptoms, including pain (Ciechanowski et al 2002, Ehnvall et al 2009, Waldinger et al 2006. Experimental studies have shown that individuals who are more sensitive to experimental pain self-report higher levels of social pain in response to social exclusion (Eisenberger et al 2006).…”
Section: Consequences Of An Overlapmentioning
confidence: 99%
“…Evidence suggests that emotional abuse, neglect, and physical and sexual abuse experienced in childhood are associated with adverse physical health outcomes in adulthood (Moeller et al 1993;Shaw and Krause 2002;Spertus et al 2003; Thompson et al 2002;Waldinger et al 2006;Walker et al 1999). For example, adult women who reported childhood sexual abuse also reported higher levels of gastrointestinal disorders, chronic pelvic pain, and other physical conditions in adulthood (Heitkemper et al 2001;Leserman et al 1996;Rimsza and Berg 1988;Walker et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Natural, as well as manmade disasters and accidents disrupt person's stability. Studies have focused on the effect of early life trauma onto stress reaction, posttraumatic stress reaction, perception of pain, somatization and dissociation (Waldinger et al 2006;Mikulincer et al1999;Luecken, 1998;Kong et al, 2017). In some cases mental health and well-being is restored shortly after experiencing traumatic event, in others, however, negative consequences develop.…”
Section: Traumamentioning
confidence: 99%